2000
DOI: 10.1152/jn.2000.83.3.1710
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+- and Metabolism-Related Changes of Mitochondrial Potential in Voltage-Clamped CA1 Pyramidal Neurons In Situ

Abstract: In hippocampal slices from rats, dialysis with rhodamine-123 (Rh-123) and/or fura-2 via the patch electrode allowed monitoring of mitochondrial potential (DeltaPsi) changes and intracellular Ca(2+) ([Ca(2+)](i)) of CA1 pyramidal neurons. Plasmalemmal depolarization to 0 mV caused a mean [Ca(2+)](i) rise of 300 nM and increased Rh-123 fluorescence signal (RFS) by Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 70 publications
4
27
0
Order By: Relevance
“…K ATP channels in brain hypoxia also not affected by depleting endoplasmic reticulum Ca 2+ stores with cyclopiazonic acid (Fig.·3C). On the contrary, the Cai response to anoxia or cyanide is both mimicked and occluded by the protonophore FCCP (Fig.·3C), which dissipates the mitochondrial transmembrane H + gradient (Schuchmann et al, 2000). These results suggest that the moderate anoxic rise of Cai is caused by mitochondrial Ca 2+ release .…”
Section: Katp Channels In Anoxia-tolerant Dorsal Vagal Neuronsmentioning
confidence: 88%
“…K ATP channels in brain hypoxia also not affected by depleting endoplasmic reticulum Ca 2+ stores with cyclopiazonic acid (Fig.·3C). On the contrary, the Cai response to anoxia or cyanide is both mimicked and occluded by the protonophore FCCP (Fig.·3C), which dissipates the mitochondrial transmembrane H + gradient (Schuchmann et al, 2000). These results suggest that the moderate anoxic rise of Cai is caused by mitochondrial Ca 2+ release .…”
Section: Katp Channels In Anoxia-tolerant Dorsal Vagal Neuronsmentioning
confidence: 88%
“…2؉ ion uptake and extrusion in changes of ⌬⌿m It was shown that changes in ⌬⌿m evoked by a prolonged (15 s) depolarization step above the threshold of Ϫ40 mV were dependent on Ca 2ϩ ion influx through voltage-gated calcium channels in pyramidal cells (Schuchmann et al, 2000). Therefore, we hypothesized that the loss of ⌬⌿m during SLE was dependent on an increase in [Ca 2ϩ ] i .…”
Section: Involvement Of Camentioning
confidence: 98%
“…To give a relative estimation of the change in ⌬⌿m, we compared SLEassociated cytosolic Rh-123 elevation with the effect of protonophore application at the end of an SLE sequence. The protonophores FCCP and CCCP were shown to completely dissipate ⌬⌿m and to increase the intensity of cytosolic Rh-123 fluorescence (Duchen, 1992;Schuchmann et al, 2000;Kovács et al, 2001). Application of a protonophore resulted in an overall increase in the cytosolic Rh-123 fluorescence by 132 Ϯ 9% (n ϭ 3 cells), whereby fluorescence of single mitochondria disappeared (Fig.…”
Section: Changes In ⌬⌿M Associated With Slesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the decreased H + conductance in response to these ATP-synthase inhibitors, mitochondria become hyperpolarized (as indicated by the monitoring of ?? m by e.g., Rh123) Schuchmann et al, 2000).…”
Section: Inhibition Of Mitochondrial Atp Synthasementioning
confidence: 99%